To Study The Vulvovaginal Candidiasis in Pregnancy With Special Reference to Cdr1 Gene in Women’s Attending a Tertiary Care Centre - Agarwal , Roli; Agarwal, Sheetal; Sharma, Sheela; Afaq, Nashra; Kumar, Deepak (Journal of Neonatal Surgery, 2025)
INTRODUCTION: Candida is the leading cause of vaginitis, and 75% of women have at least one episode in their lifetimes. Candida colonisation in vagina was reported to be 20 %, rising to 30 % during pregnancy. Studies show that pregnant women with VVC are more likely than healthy women to have it. Both symptomatic and asymptomatic candidal colonisation rises throughout pregnancy. It is unknown, therefore, how strains that produce silent infection vary from those that cause symptomatic infection. AIM AND OBJECTIVE: To study the vulvovaginal candidiasis in pregnancy with special reference to CDR1 gene in women’s attending a tertiary care centre. MATERIAL AND METHODS: This was a cross sectional study conducted in the Department of Microbiology at a tertiary care centre. A total of 962 clinical samples were screened. The Culture identification, specification, Antifungal Susceptibility testing was performed according to the CLSI guidelines. The DNA was extracted using the Qiagen DNA extraction kit and the resistant gene CDR1 was detected using the PCR. RESULTS: In the present study out of 962 clinical samples, 51.1% (492) were culture positive, among them 28% (138) were Candida isolates. Out of which 53(38.4%) were Candida albicans while 85(61.6%) were Non-albicans Candida. Among Non-albicans Candida,the frequency of Candida tropicalis was observed to be maximum with urine samples and least for ET secreation. It was observed that the maximum sensitivity was observed with Amphotericin-B (95%), followed by Voriconazole(85%) and itraconazole (49.2%). The prevalence of CDR1 expression was 4.3% among Candida spp. CONCLUSION: Characterising the virulence factors in Candida species that have been isolated from a range of clinical specimens will help us better understand the pathophysiology and clinical outcomes of candidiasis. Further research is required to improve patient outcomes in clinical practice and address the evolving issues brought on by Candida infections. By considering the interplay of genetic changes, phenotypic characteristics, and patient-related factors, azole resistance can be evaluated more thoroughly.